Infanticide and Filicide : Foundations in Maternal Mental Health Forensics. - Wong, Gina, 1971- (American Psychiatric Association Publishing, 2020)
Infanticide and Filicide reveals new insights and recollections of George Parnham, the attorney who successfully defended Yates. It also delves into research and the practical application of maternal mental health forensics, and offers a thorough description of current theory, bolstered by more than 30 experts in the field representing eight countries, and provides real case examples. A chapter on fathers who commit filicide, a subject that receives far less attention in research, is also included.